Associations between gait speed, grip force and executive function in young individuals with down syndrome. - Chen, Chih-Chia; Ringenbach, Shannon (International Journal of Developmental Disabilities, 2026)
The association between motor and executive function have been systematically examined in general populations; however, relevant studies that focus on individuals with Down syndrome (DS) are still limited. The purpose of the study examined the relationships between grip strength, gait speed, and executive function in young individuals with DS. Twenty adolescents and young adults with DS, aged 13–29, participated in the present study. Participants completed multiple measures for motor function (i.e. grip strength and gait speed) and executive function (i.e. dimensional card sorting, verbal fluency, and knock-tap tests). Results indicated that participants with DS who had stronger grip force had better performance in inhibitory function. In addition, participants with DS who had faster gait speed had better performance in verbal fluency skills. Motor and executive functions seem to be linked in participants with DS. Thus, grip strength and gait speed may be convenient clinical attributes that predict executive function alterations in individuals with DS. Based on the results, it is suggested that individuals with DS may gain cognitive benefits by participating in interventions that target specific motor functions.